ANALISIS KESALAHAN BERBAHASA INDONESIA PADA PAPAN SPANDUK DI SEPUTARAN LINGKUNGAN KOTA BATAM - Telutci, Telutci; Oktavia, Yunisa (eScience Humanity Journal, 2022)
The aim is to find out the writing on the banner to get pictures or photos on the banner to see in this case which vocabulary and sentences are wrong on the banner and to get information that can be processed as material for making scientific articles, which consists of the basic theory of the language used is far from the norm. This case is caused by the lack of public understanding of language and writing in the use of words according to the KBBI which uses vocabulary and is structured in sentences. In producing data sources obtained from the surrounding environment to be able to take data such as interviews with people who are responsive around the environment to obtain accurate data as material for scientific works. The perfection and correctness of linguistic basics in language use errors were found around the banner, from the results of research in the use of descriptive methods in language use errors found in research as objects and research subjects on banners in data recording is observed in case studies used in writing the results of the study indicate that the writing on the banner uses informal language in the form of various written languages ​​depending on the inappropriate writing style. According to the rules. From the results of the study, it was found that there was a lot of error information on language users on banners in grouping sentences and vocabulary based on factual information in processing data as an object of analysis in solving Indonesian.